A perovskite solar cell modified by benzothiadiazole-4,7-dicarbohydrazide, a laminated solar cell and a preparation method
Patent Information
- Application Number
- CN202611406244.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-13
AI Technical Summary
然而,常规添加剂在宽带隙体系中常常功能单一,难以兼顾多重需求:能够有效钝化铅相关缺陷的分子往往缺乏对卤素离子的强锚定作用,无法阻断相分离;而能抑制离子迁移的交联剂又可能增大薄膜残余应力或引入新的界面缺陷
1、本发明通过在钙钛矿活性层中引入苯并噻二唑-4,7-二甲酰肼,利用其“多位一体”的协同机制全面优化器件性能:分子两端的双酰肼基团调控成核动力学,促进钙钛矿沿(100)晶面择优取向生长,改善晶格有序性;同时,苯并噻二唑环上的S、N原子与酰肼基团构成S/N/O多齿配位网络,对欠配位Pb2+实现强力螯合锚定;此外,丰富的N-H结构单元通过强氢键作用同步捕获Br-。基于上述协同作用,本发明大幅降低了深能级缺陷态密度,有效阻断了非辐射复合与离子迁移,实现了器件光电转换效率与长期运行稳定性的同步提升。
Smart Images

Figure CN122909960A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of perovskite photovoltaic technology, and relates to a perovskite solar cell modified with benzothiadiazole-4,7-dicarboxyhydrazide, a tandem solar cell, and a method for its preparation. Background Technology
[0002] Perovskite solar cells, with their excellent photoelectric properties and low-cost fabrication advantages, have become a core research direction in next-generation photovoltaic technology. To overcome the efficiency limit of single-junction cells, all-perovskite tandem solar cells, by connecting a wide-bandgap top cell and a narrow-bandgap bottom cell in series, can fully utilize the solar spectrum, thereby improving efficiency and demonstrating enormous application potential. Among these, wide-bandgap perovskite with a bandgap in the range of 1.65–1.85 eV is the core material for tandem top cells.
[0003] However, widening the bandgap to this range typically requires a significant increase in the bromine content of the halogen component, which inevitably raises several closely related and severe challenges. First, high-bromine-content mixed-halogen perovskites are highly susceptible to severe halide photo-induced phase separation under illumination or electric field driving—iodine and bromide ions undergo spatial redistribution, forming iodine-rich and bromine-rich domains. This not only leads to spontaneous bandgap contraction and energy level mismatch but also causes an anomalous redshift of the photoluminescence peak and a significant decrease in external quantum efficiency, resulting in severe open-circuit voltage deficit. Second, wide-bandgap perovskite films often generate high-density deep-level defects (such as undercoordinated lead clusters and halogen interstices) during rapid crystallization. These deep-level defects become strong nonradiative recombination centers, significantly increasing carrier losses and accelerating ion migration, causing a sharp deterioration in both device efficiency and long-term operational stability. Third, iodine ions (I₂O₃)... - Migration and oxidation under light and thermal stress (I) - →I2) can cause irreversible material degradation and performance decline. Therefore, how to synergistically suppress halide phase separation, significantly reduce defect state density, and block iodine ion migration while maintaining a wide bandgap has become a core bottleneck that urgently needs to be overcome in this field.
[0004] Additive engineering, due to its simple process and significant effects, has been widely used to regulate perovskite crystallization kinetics, passivate defects, and inhibit ion migration. However, conventional additives in wide bandgap systems often have a single function and cannot meet multiple needs simultaneously: molecules that can effectively passivate lead-related defects often lack strong anchoring effects on halide ions and cannot block phase separation; while crosslinking agents that can inhibit ion migration may increase residual stress in the film or introduce new interfacial defects.
[0005] To address the shortcomings of existing additive modification technologies, which have a single modification dimension, there is an urgent need to develop a novel organic additive with multiple coordination sites to simultaneously solve the performance bottleneck of high-bromine wide-bandgap perovskites from multiple dimensions. Summary of the Invention
[0006] In view of the problems existing in the prior art, the purpose of the present invention is to provide a perovskite solar cell modified with benzothiadiazole-4,7-dicarboxyhydrazide, a tandem solar cell and a method for its preparation. The use of benzothiadiazole-4,7-dicarboxyhydrazide as an additive for the perovskite active layer is beneficial to improving the photoelectric conversion efficiency and stability of wide-bandgap perovskite solar cell devices and all-perovskite tandem devices.
[0007] The present invention employs the following technical solutions to achieve its objective: The first aspect of this invention provides a perovskite solar cell modified with benzothiadiazole-4,7-dicarboxyhydrazide, comprising a substrate, a first hole transport layer, a first perovskite active layer, a first electron transport layer, a first electron modification layer, and a first electrode, which are sequentially stacked; the first perovskite active layer contains benzothiadiazole-4,7-dicarboxyhydrazide, and the molecular structure of benzothiadiazole-4,7-dicarboxyhydrazide is as follows: ; The perovskite solar cell is a wide-bandgap perovskite solar cell, and the optical bandgap of its first perovskite active layer is 1.65~1.85 eV.
[0008] The wide-bandgap perovskite solar cell has a perovskite active layer bandgap of 1.65~1.85 eV. To achieve this wide bandgap range, the proportion of bromide ions in the perovskite lattice is relatively high. The high-bromine system leads to multiple defects such as halide photo-induced phase separation, high-density deep-level defects, and halide ion migration. Benzothiadiazole-4,7-dicarboxyhydrazide is used as an additive, which has a conjugated framework, multidentate coordination sites, and hydrogen bonding groups, and can specifically suppress and passivate various defects corresponding to high-bromine wide-bandgap perovskites. It mainly optimizes device performance through the following four-in-one synergistic mechanism: (1) π-π conjugated framework promotes interfacial charge transfer: The rigid planar π-conjugated system provided by the BTD core constructs an effective charge transfer bridging channel at the interface between the perovskite active layer and the electron transport layer, which significantly reduces the interfacial transport barrier and is conducive to the efficient extraction of photogenerated carriers.
[0009] (2) S / N multi-tooth coordination synergistic anchoring of Pb 2+ The sulfur (S) atom on the benzothiadiazole ring and the nitrogen (N) atom within the ring act as embedded Lewis base sites, forming an S / N / O polydentate coordination network together with the carbonyl oxygen and terminal amino nitrogen in the hydrazide groups at both ends. This network, through a multi-site synergistic coordination effect, coordinates the undercoordinated Pb... 2+ Ions achieve strong chelation and anchoring, and their passivation ability is far superior to that of a single functional group, thereby significantly reducing the density of deep-level trap states.
[0010] (3) Dihydrazide regulates crystallization and synergistically fixes Pb 2+ With Br - The two hydrazide groups at both ends of the molecule not only promote the preferred orientation growth of perovskite along the (100) crystal plane by regulating nucleation kinetics, thereby improving lattice order and reducing defect state density, but also provide additional coordinating atoms to fix Pb. 2+ Its abundant NH structural units also simultaneously capture and anchor halide ions (especially Br) through strong hydrogen bonding. - This effectively inhibits the long-range migration and photo-induced phase separation of halides in high-bromine content systems, thereby stabilizing the lattice and band gap of wide-bandgap perovskites from the root.
[0011] (4) Interface dipole optimization of electron transport: The combination of π-π conjugated framework and polar hydrazide group gives the molecule a suitable dipole moment, optimizes the energy level arrangement of the perovskite / electron transport layer interface, further reduces the interface contact resistance, and improves the electron injection efficiency.
[0012] The synergistic effect of the above multiple effects significantly improves the crystal quality, defect passivation effect, ion migration suppression ability and interfacial charge transfer kinetics of wide-bandgap perovskite films, effectively improving the photoelectric efficiency of perovskite solar cells.
[0013] The substrate, first hole transport layer, first electron transport layer, first electron modification layer, and first electrode described herein are all common materials for perovskite solar cells in this field. All similar materials that can be adapted to perovskite solar cells fall within the protection scope of this invention, and are not limited to the following listed types.
[0014] For example, the substrate is conductive glass.
[0015] For example, the material of the first hole transport layer is selected from nickel oxide (NiO). x The following are some of the following: poly(4-phenyl)(2,4,6-trimethylphenyl)amine (PTAA), poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS), poly(3-hexylthiophene-2,5-diyl) (P3HT), and self-assembled monomolecular materials (SAM); wherein the self-assembled monomolecular material is one or more of [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz), (2-(9H-carbazole-9-yl)ethyl)phosphonic acid (2PACz), (3-(9H-carbazole-9-yl)propyl)phosphonic acid (3PACz), (3-(9H-carbazole-9-yl)butyl)phosphonic acid (4PACz), and (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid (MeO-2PACz).
[0016] For example, the material of the first electron transport layer is fullerene C. 60 It is one or more of the following: its derivatives, titanium dioxide, and tin dioxide. Preferably, the thickness of the first electron transport layer is 10-50 nm.
[0017] For example, the material of the first electronic modification layer is one or more of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP), 4,7-diphenyl-1,10-phenanthroline, SnO2, ZnO, and TiO2, and the thickness of the first electronic modification layer is 2~10 nm.
[0018] For example, the first electrode is a metal electrode or a carbon electrode. Preferably, the thickness of the first electrode is 50~200 nm.
[0019] Preferably, the material of the first perovskite active layer includes benzothiadiazole-4,7-dicarboxyhydrazide and a material with the general formula FA. 1-x-y Cs x MA y PbI 3-z-a Br z Cl a The perovskite material has a high Br content. After adding benzothiadiazole-4,7-dicarboxyhydrazide of the present invention, its terminal NH structural units can simultaneously capture and anchor Br through strong hydrogen bonding. - It effectively inhibits the long-range migration and photo-induced phase separation of halides in high-bromine content systems, thereby stabilizing the lattice and band gap of wide-bandgap perovskites from the root.
[0020] Preferably, the first perovskite active layer is formed by coating a first perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide; the concentration of benzothiadiazole-4,7-dicarboxyhydrazide in the first perovskite precursor solution is 0.1~5.0 mg / mL, and can be listed as any value selected from 0.1 mg / mL, 0.2 mg / mL, 0.3 mg / mL, 0.5 mg / mL, 0.8 mg / mL, 1.0 mg / mL, 1.5 mg / mL, 2.0 mg / mL, 2.5 mg / mL, 3.0 mg / mL, 3.5 mg / mL, 4.0 mg / mL, 4.5 mg / mL, or 5.0 mg / mL. More preferably, the concentration of benzothiadiazole-4,7-dicarboxyhydrazide is 0.5~3.0 mg / mL. When the doping concentration is too low, the multidentate coordination network cannot completely cover the perovskite grain boundaries and bulk defects; when the concentration is too high, molecular aggregation may occur at the grain boundaries, which may hinder carrier transport.
[0021] Preferably, the preparation method of the benzothiadiazole-4,7-dicarboxyhydrazide includes the following steps: (1) Benzothiadiazole-4,7-dicarboxylic acid reacts with an alcohol solvent under the catalysis of an acid catalyst to give an intermediate product; (2) Dissolve the intermediate product obtained in step (1) in an organic solvent, add hydrazine hydrate, and carry out hydrazinolysis to obtain benzothiadiazole-4,7-dicarboxyhydrazide.
[0022] Preferably, the alcohol solvent in step (1) is a C1-C4 aliphatic monohydric alcohol, and the C1-C4 aliphatic monohydric alcohol includes one or more of methanol, ethanol, n-propanol, isopropanol, and n-butanol.
[0023] Preferably, the acid catalyst comprises concentrated sulfuric acid and / or concentrated hydrochloric acid. The concentrated sulfuric acid and concentrated hydrochloric acid are commercially available products, with the concentrated sulfuric acid having a mass fraction of 95-98 wt% and the concentrated hydrochloric acid having a mass fraction of 35-38 wt%.
[0024] Preferably, in step (1), the molar ratio of benzothiadiazole-4,7-dicarboxylic acid to the acid catalyst is 1:(1~3); the esterification reaction temperature is 50~80℃, the reaction time is 8~16h, and reflux heating is preferred; the reaction process is monitored by thin-layer chromatography during the reaction, and the reaction is stopped after the raw materials have reacted completely.
[0025] Preferably, after the esterification reaction in step (1) is completed, the reaction solution is cooled to room temperature, the alcohol solvent is removed by vacuum distillation, the residue is added to ice water at 0~5°C, the solid is precipitated and then filtered, the filter cake is washed with water and dried to obtain the intermediate product.
[0026] Preferably, in step (2), the organic solvent is one or more of methanol, ethanol, n-propanol, isopropanol, and n-butanol.
[0027] Preferably, in step (2), the hydrazine hydrate is an aqueous solution of hydrazine hydrate with a mass fraction of 50~85wt%; the molar ratio of the intermediate product to hydrazine hydrate is 1:(5~10).
[0028] Preferably, in step (2), the reaction temperature of the hydrazine hydrolysis reaction is 60~80℃ and the reaction time is 6~12h, preferably using reflux heating; the reaction process is monitored by thin-layer chromatography and the reaction is stopped after the raw materials disappear.
[0029] Preferably, after the hydrazine hydrolysis reaction in step (2) is completed, the reaction solution is cooled to room temperature, the solvent is removed by vacuum distillation, and the residue is recrystallized using a recrystallization solvent. After drying, benzothiadiazole-4,7-dicarboxyhydrazide is obtained. The recrystallization solvent is an alcohol solvent, including one or more of methanol, ethanol, n-propanol, isopropanol, and n-butanol.
[0030] A second aspect of the present invention provides a method for preparing the above-mentioned benzothiadiazole-4,7-dicarboxyhydrazide-modified perovskite solar cell, comprising the following steps: S1. Prepare the first hole transport layer on the substrate; S2. Prepare a first perovskite precursor solution by adding benzothiadiazole-4,7-dicarboxyhydrazide to the first perovskite precursor solution and mixing it evenly to obtain a first perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide. S3. Spin-coating a first perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide onto the surface of the first hole transport layer, followed by annealing to form the first perovskite active layer. S4. A first electron transport layer, a first electron modification layer and a first electrode are sequentially prepared on the first perovskite active layer to obtain the perovskite solar cell.
[0031] Preferably, the solvent of the first perovskite precursor solution is a polar aprotic organic solvent selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.
[0032] Preferably, in the first perovskite precursor solution, Pb 2+ The concentration is 0.5~2.0 mol / L. In the first perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide, the concentration of benzothiadiazole-4,7-dicarboxyhydrazide is 0.1~5.0 mg / mL.
[0033] Preferably, in step S3, the spin coating adopts a two-step spin coating process: the first step is spin coating at 400~1000 rpm for 1~10 s, and the second step is spin coating at 3000~5000 rpm for 40~70 s, and the anti-solvent is added dropwise at the 20~30 s of the second spin coating; the anti-solvent is selected from one or more of ethyl acetate, chlorobenzene, toluene, and anhydrous diethyl ether.
[0034] Preferably, the annealing treatment is performed at a temperature of 100~140℃ for a time of 10~30 min.
[0035] The first electron transport layer, the first electron modification layer, and the first electrode are obtained by vacuum thermal evaporation deposition.
[0036] A third aspect of the present invention provides an all-perovskite tandem solar cell, comprising a top cell sub-unit, an intermediate interconnect layer, and a bottom cell stacked sequentially. The top-mounted battery sub-unit includes a substrate, a first hole transport layer, a first perovskite active layer, and a first electron transport layer stacked sequentially. The first perovskite active layer contains benzothiadiazole-4,7-dicarboxyhydrazide, and the optical band gap of the first perovskite active layer is 1.65~1.85 eV. The bottom cell includes a second hole transport layer, a second perovskite active layer, a second electron transport layer, a second electron modification layer, and a second electrode, which are stacked sequentially; the optical band gap of the second perovskite active layer is 1.2~1.4 eV; The intermediate interconnect layer is stacked on the surface of the first electron transport layer of the top battery sub-cell.
[0037] The intermediate interconnect layer uses common interconnect materials for all-perovskite tandem solar cells in the field, preferably tin oxide and / or gold layers.
[0038] The second hole transport layer is located on the intermediate interconnect layer.
[0039] In this paper, the second hole transport layer, the second perovskite active layer, the second electron transport layer, the second electron modification layer, and the second electrode are all common materials for perovskite solar cells in the field. All similar materials that can be adapted to perovskite cells fall within the protection scope of this invention, and are not limited to the following listed types.
[0040] By way of example, the material of the second hole transport layer is selected from one or more of poly[3-(4-carboxybutyl)thiophene] (P3CT), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS), and poly(3-hexylthiophene-2,5-dimethyl) (P3HT).
[0041] For example, the material of the second electron transport layer is fullerene C. 60 It is one or more of the following: its derivatives, titanium dioxide, and tin dioxide. Preferably, the thickness of the second electron transport layer is 10-50 nm.
[0042] By way of example, the second electrode is a metal electrode or a carbon electrode. Preferably, the thickness of the second electrode is 50~200 nm.
[0043] For example, the material of the second electronic modification layer is one or more of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP), 4,7-diphenyl-1,10-phenanthroline, SnO2, ZnO, and TiO2, and the thickness of the second electronic modification layer is 2~10 nm.
[0044] Preferably, the material of the second perovskite active layer is of general formula FA. 1-x-y Cs x MA y Pb 1-b Sn b I 3-z-a Br z Cl a The perovskite material, wherein 0≤x≤0.4, 0≤y≤0.4, 0<b≤0.6, 0≤z≤1.5, 0≤a≤1.5.
[0045] Preferably, the bottom cell further includes a perovskite modification layer located between the second perovskite active layer and the second electron transport layer.
[0046] Preferably, the materials of the perovskite modification layer include ethylenediamine dihydroiodide and 1,4-butanediamine hydroiodide.
[0047] A fourth aspect of this invention provides a method for fabricating an all-perovskite tandem solar cell, comprising the following steps: S1. Prepare the first hole transport layer on the substrate; S2. Prepare a first perovskite precursor solution by adding benzothiadiazole-4,7-dicarboxyhydrazide to the first perovskite precursor solution and mixing it evenly to obtain a first perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide. S3. Spin-coating a first perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide onto the surface of the first hole transport layer, followed by annealing to form the first perovskite active layer. S4. Prepare the first electron transport layer on the first perovskite active layer to obtain the top cell sub-unit; S5. An intermediate interconnect layer is fabricated on the surface of the first electron transport layer of the top battery sub-cell; S6. Prepare a second hole transport layer on the surface of the intermediate interconnect layer, and then deposit a second perovskite active layer. S7. A second electron transport layer, a second electron modification layer and a second electrode are sequentially prepared on the surface of the second perovskite active layer to obtain a fully perovskite tandem solar cell.
[0048] The second electron transport layer, the second electron modification layer, and the second electrode were obtained by vacuum thermal evaporation deposition.
[0049] When the bottom cell also includes a perovskite modification layer, step S7 includes: sequentially preparing a perovskite modification layer, a second electron transport layer, a second electron modification layer and a second electrode on the surface of the second perovskite active layer to obtain a fully perovskite tandem solar cell.
[0050] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention optimizes device performance by introducing benzothiadiazole-4,7-dicarboxyhydrazide into the perovskite active layer, utilizing its "multi-dimensional" synergistic mechanism: the dihydrazide groups at both ends of the molecule regulate the nucleation kinetics, promoting the preferred orientation growth of perovskite along the (100) crystal plane and improving lattice order; simultaneously, the S and N atoms on the benzothiadiazole ring and the hydrazide groups form an S / N / O multidentate coordination network, which improves the coordination of undercoordinated Pb. 2+ Achieving strong chelation and anchoring; in addition, abundant NH structural units simultaneously capture Br through strong hydrogen bonding. - Based on the aforementioned synergistic effect, this invention significantly reduces the density of deep-level defect states, effectively blocks non-radiative recombination and ion migration, and achieves a simultaneous improvement in device photoelectric conversion efficiency and long-term operational stability.
[0051] 2. The single-junction wide-bandgap perovskite solar cell prepared by the method of the present invention has a significantly weakened hysteresis effect and higher open-circuit voltage and photoelectric conversion efficiency. Furthermore, when it is used as the top cell in an all-perovskite tandem solar cell, it effectively reduces the non-radiative recombination loss at the interface, improves the total open-circuit voltage, short-circuit current density and fill factor of the tandem device, and enables the photoelectric conversion efficiency of the tandem device to successfully exceed 30%.
[0052] 3. The benzothiadiazole-4,7-dicarboxyhydrazide of this invention exhibits excellent system universality, applicable to wide-bandgap perovskite systems of different compositions with band gaps ranging from 1.65 to 1.85 eV, providing a general strategy for performance optimization of various wide-bandgap optoelectronic devices. Furthermore, benzothiadiazole-4,7-dicarboxyhydrazide is only distributed at grain boundaries and interfaces, does not participate in perovskite lattice substitution, and does not change the intrinsic band gap of the material, thus exhibiting good compatibility with existing perovskite preparation processes.
[0053] 4. The preparation method of this invention has controllable parameters, is easy to operate, and has good repeatability. It is perfectly compatible with the existing mainstream anti-solvent two-step spin coating method, does not require the use of complex additional production equipment, has a simple overall process flow, and is very suitable for large-scale industrial production. It has extremely high commercial conversion and application prospects in the field of high-efficiency all-perovskite tandem photovoltaics. Attached Figure Description
[0054] Figure 1 A schematic diagram of the structure of the inverted wide-bandgap perovskite solar cell device prepared in Example 1 of this invention; Figure 2 These are the JV curves of the wide-bandgap perovskite solar cells prepared in Example 1 and Comparative Example 1 of this invention; Figure 3 These are the steady-state fluorescence spectra of the wide-bandgap perovskite solar cells prepared in Example 1 and Comparative Example 1 of this invention; Figure 4 This is a schematic diagram of the structure of the all-perovskite tandem solar energy device prepared in Example 2 of the present invention; Figure 5 These are the JV curves of the all-perovskite tandem solar cells prepared in Example 2 and Comparative Example 2 of this invention; Figure 6 These are the JV curves of the wide-bandgap perovskite solar cells with a bandgap of 1.68 eV prepared in Example 3 and Comparative Example 3 of this invention. Figure 7 These are the JV curves of the wide bandgap perovskite solar cells with a bandgap of 1.85 eV prepared in Example 4 and Comparative Example 4 of this invention. Detailed Implementation
[0055] In the description of this invention, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, and includes both a and b. "Multiple" includes two or more types, and can be two, three, four, five, or more.
[0056] The technical solution of the present invention will be further described and illustrated below with reference to specific embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are only for the purpose of helping to understand the present invention and are not intended to limit the specific scope of the present invention. Furthermore, the accompanying drawings used herein are merely for better illustrating the content disclosed in the present invention and do not limit the scope of protection. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used in the art, and the methods used in the embodiments are all conventional methods in the art.
[0057] In the following examples and comparative examples, benzothiadiazole-4,7-dicarboxyhydrazide was prepared by the following method: (1) Synthesis of methyl benzothiadiazole-4,7-dicarboxylate Commercially available benzothiadiazole-4,7-dicarboxylic acid (CAS: 5170-41-2) was used as the starting material. In a 100 mL single-necked round-bottom flask, benzothiadiazole-4,7-dicarboxylic acid (2.24 g, 10 mmol) and anhydrous methanol (30 mL) were added. Concentrated sulfuric acid (1.0 mL, approximately 18 mmol) was slowly added dropwise as a catalyst while stirring. After the addition was complete, the mixture was heated to 65 °C and refluxed for 12 hours. Thin-layer chromatography (TLC, eluent: ethyl acetate to petroleum ether, volume ratio 1:2) was used to monitor the reaction until the starting material was completely reacted. After cooling the reaction solution to room temperature, most of the methanol was evaporated under reduced pressure. The residue was slowly poured into 50 mL of ice water at 0 °C, precipitating a pale yellow solid. The solid was filtered, and the filter cake was washed three times with deionized water (20 mL each time). After drying, the pale yellow solid product, methyl benzothiadiazole-4,7-dicarboxylate, was obtained.
[0058] (2) Synthesis of benzothiadiazole-4,7-dicarboxyhydrazide In a 100 mL three-necked flask, methyl benzothiadiazole-4,7-dicarboxylate (2.52 g, 10 mmol) obtained in the previous step and 50 mL of anhydrous methanol were added and stirred to dissolve. Hydrazine hydrate (80% aqueous solution, 4.8 mL, 80 mmol) was slowly added dropwise. After the addition was complete, the mixture was heated to 70 °C and refluxed for 8 hours. Thin-layer chromatography (TLC, developing solvent: ethyl acetate to methanol, volume ratio 5:1) was used to monitor the reaction until the starting material disappeared. The reaction solution was cooled to room temperature, the solvent was removed under reduced pressure, and the residue was recrystallized from ethanol and dried to give the pale yellow solid target product, benzothiadiazole-4,7-dicarboxyhydrazide.
[0059] Example 1: Fabrication of a single-junction wide-bandgap perovskite solar cell
[0060] S1: The etched ITO / glass substrate (a composite substrate formed by depositing ITO on a glass surface) is sequentially cleaned for 30 minutes with detergent, deionized water, acetone, and isopropanol. The cleaned substrate is then dried with N2 gas. After drying, the substrate is treated with air-plasma plasma (plasma generated using air as the working gas) for 5 minutes, and then a layer of NiO is coated onto the ITO glass substrate. X An aqueous solution (10 mg / mL) was spin-coated at 1500 rpm for 30 s, followed by annealing in air at 150 °C for 10 min and cooling. The resulting substrate was transferred to a glove box filled with N2 (O2 < 0.1 ppm, H2O < 0.1 ppm). Under an N2 atmosphere, an ethanol solution (0.5 mg / mL) of [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz) was used as a hole transport layer and spin-coated at 3000 rpm onto NiO. X Spin coat the surface for 30 seconds, then anneal at 100°C for 10 minutes.
[0061] S2: Deposition of wide-bandgap perovskite films using a two-step spin-coating process: In a glove box, 70 μL of a perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide was spin-coated at 500 rpm for 2 s, followed by spin-coating at 4000 rpm for 60 s. In the second spin-coating step, 150 μL of ethyl acetate as an antisolvent was added dropwise at 25 s. The mixture was then thermally annealed at 120 °C for 20 min in a N2 atmosphere to form a perovskite film containing benzothiadiazole-4,7-dicarboxyhydrazide with the molecular formula FA. 0.8 Cs 0.2 PbI 1.8 Br 1.2 The perovskite layer. The perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide was prepared as follows: N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) were mixed in a volume ratio of 4:1 to prepare a mixed solvent. Then, FAI (165.1 mg), PbBr2 (264.2 mg), PbI2 (221.3 mg), PbCl2 (6.67 mg), CsI (62.4 mg), and MACl (1.62 mg) were dissolved in 1 mL of the mixed solvent to form a perovskite precursor solution with a concentration of 1.2 mol / L. Then, benzothiadiazole-4,7-dicarboxyhydrazide was dissolved in the prepared perovskite precursor solution at a concentration of 1.0 mg / mL. The solution was filtered through a 0.22 μm polytetrafluoroethylene (PTFE) membrane before use.
[0062] S3: After annealing and cooling in step S2, the vacuum degree is not less than 1×10 -4 Under Pa conditions, C with a thickness of 25 nm was sequentially deposited using a vacuum evaporation equipment. 60 An electron transport layer, a 7 nm thick BCP electron modification layer, and then a 100 nm thick silver electrode are deposited under vacuum to assemble a single-junction wide-bandgap perovskite solar cell device. For example... Figure 1 As shown, the fabricated single-junction wide-bandgap perovskite solar cell device, from bottom to top, comprises: an ITO glass substrate, a hole transport layer NiO, and so on. X / Me-4PACz, perovskite active layer (FA) 0.8 Cs 0.2 PbI 1.8 Br 1.2 +benzothiadiazole-4,7-dicarboxyhydrazide), electron transport layer C 60 Electronic modification layer BCP, silver electrode.
[0063] Comparative Example 1 The difference between the fabrication of the single-junction wide-bandgap perovskite solar cell in Comparative Example 1 and Example 1 is that in step S2 of Comparative Example 1, the perovskite precursor solution used did not contain benzothiadiazole-4,7-dicarboxyhydrazide, and a two-step spin-coating process was directly performed using a perovskite precursor solution with a concentration of 1.2 mol / L to deposit the wide-bandgap perovskite thin film. Everything else was the same as in Example 1.
[0064] The band gap of both Comparative Example 1 and Example 1 was measured to be 1.77 eV, indicating that the additives did not participate in the substitution or alloying of the perovskite lattice, but rather functioned as grain boundary and interface modifications. The specific band gap testing method included: depositing the perovskite films of Example 1 and Comparative Example 1 on an ITO conductive glass substrate; placing the samples in a spectrophotometer; and recording their absorption spectra in the wavelength range of 400 to 900 nanometers. After obtaining the absorption spectra, the values were plotted with photon energy (hν) on the x-axis and (αhν) on the y-axis. 2 Plot a Tauc diagram with α as the ordinate (where α is the absorption coefficient). Finally, find the region of most significant linear change in the diagram and extrapolate this linear portion to the horizontal axis. The coordinates of its intersection with the horizontal axis are the band gap value of the perovskite material.
[0065] The perovskite solar cells prepared in Example 1 and Comparative Example 1 were subjected to forward and reverse sweep JV performance tests between 0 V and 1.4 V (at a standard solar spectrum of AM 1.5G and a light intensity of 100 mW / cm²). 2 (Tests were conducted under simulated sunlight conditions). The results show that the hysteresis effect of the device in Example 1 is significantly weakened compared to Comparative Example 1, indicating a reduction in non-radiative recombination in the device. The JV test diagram is shown below. Figure 2 The performance data are shown in Table 1: After modification with benzothiadiazole-4,7-dicarboxyhydrazide, the efficiency of the 1.77 eV bandgap device is significantly improved.
[0066] Table 1 Performance data of solar cells prepared in Example 1 and Comparative Example 1
[0067] Steady-state fluorescence spectroscopy (PL) tests were performed on the solar cells obtained in Example 1 and Comparative Example 1. Figure 3 Steady-state PL spectroscopy showed that the PL peak intensity of the battery device prepared in Example 1 was significantly higher than that of the unmodified Comparative Example 1, indicating that the modification of benzothiadiazole-4,7-dicarboxyhydrazide improved the quality of the perovskite film and effectively suppressed non-radiative recombination.
[0068] Example 2: Fabrication of an all-perovskite tandem solar cell
[0069] S1-S2: Same as steps S1-S2 in Example 1.
[0070] S3: After annealing and cooling in step S2, the vacuum degree is not less than 1×10 -4 Under Pa conditions, C with a thickness of 25 nm was sequentially deposited using a vacuum evaporation equipment. 60 An electron transport layer was constructed; then a 20 nm thick SnO2 layer was deposited on the thin film via ALD; subsequently, an electron transport layer was constructed under a vacuum of not less than 1 × 10⁻⁶. -4 An Au buffer layer with a thickness of 1 nm was formed by vacuum evaporation under a Pa environment.
[0071] S4: The device obtained in step S3 was then transferred to an N2 glove box for further spin coating. P3CT solution (3 mg / ml) was spin-coated onto the top of the device obtained in step S3 at 2000 rpm for 30 s, and annealed at 100 °C for 10 min. Preparation of a 1.25 eV narrow bandgap perovskite precursor: 507.10 mg PbI2, 409.77 mg SnI2, 224.56 mg FAI, 104.92 mg MAI, 57.16 mg CsI, 17.23 mg SnF2, and 3.14 mg NH4SCN were dissolved in 1 mL of DMF and DMSO (DMF:DMSO = 3:1, v / v), and the mixture was stirred for 12 h to prepare a 2.2 mol / L narrow bandgap perovskite precursor. The solution was filtered through a 0.22 μm polytetrafluoroethylene (PTFE) membrane before use. A two-step spin-coating method was used: 1000 rpm for 10 s, 4000 rpm for 30 s. At the 30th s mark of the second spin-coating step, 400 μL of the antisolvent chlorobenzene (CB) was added dropwise, followed by annealing at 100 °C for 10 min. Then, a modification solution of ethylenediamine dihydroiodide (EDAI2) and 1,4-butanediamine hydroiodide (BDADI) (EDAI2 and BDADI were mixed at a molar ratio of 10:1, dissolved in IPA, with an EDAI2 concentration of 1.0 mg / mL) was spin-coated at 2000 rpm for 20 s, followed by annealing at 100 °C for 5 min. Finally, 25 nm C₂ was deposited sequentially using a vacuum thermal evaporation method. 60 Using 6nm BCP and 100nm Ag, a fully perovskite tandem solar cell was fabricated. Its structural schematic is shown in [Figure number missing]. Figure 4 .
[0072] Comparative Example 2 The difference between the preparation of the all-perovskite tandem solar cell in Comparative Example 2 and Example 2 is that in step S2 of Comparative Example 2, the perovskite precursor solution used did not contain benzothiadiazole-4,7-dicarboxyhydrazide, and a wide-bandgap perovskite thin film was deposited directly using a two-step spin-coating process with a perovskite precursor solution of concentration of 1.2 mol / L. All other steps were the same as in Example 2.
[0073] JV performance tests were performed on the packaged stacked devices of Example 2 and Comparative Example 2. The tests were conducted in both forward and reverse sweeps within the voltage range of 0 V–2.2 V. The test results are as follows. Figure 5 As shown in Table 2, the photoelectric conversion efficiency and open-circuit voltage of the all-perovskite tandem solar cell were significantly improved after modification with benzothiadiazole-4,7-dicarboxyhydrazide. The efficiency of the modified tandem device increased from 27.2992% in the control group to 30.3502%, and the open-circuit voltage increased from 2.1207 V to 2.1619 V. The fill factor and short-circuit current density were also improved simultaneously, indicating that nonradiative recombination and interface charge accumulation in the device were effectively suppressed.
[0074] Table 2 Performance data of solar cells prepared in Example 2 and Comparative Example 2
[0075] The performance improvement of all-perovskite tandem solar cells can be attributed to the multi-layered optimization of the wide-gap top cell by benzothiadiazole-4,7-dicarboxyhydrazide, which is then transferred to the entire tandem device: First, the S / N / O multidentate coordination network optimizes the Pb content in the top cell. 2+ The efficient passivation of related defects significantly reduces the open-circuit voltage deficit of wide-bandgap cells, directly increasing the total open-circuit voltage of stacked devices; secondly, the dihydrazide's effect on Br - The hydrogen bond fixation effectively suppresses halide phase separation during the thermal annealing process of the top cell in the tandem fabrication, ensuring the stability of the top cell bandgap and the efficient generation of photogenerated carriers. Furthermore, the π-conjugated framework of the BTD core not only optimizes the charge extraction kinetics within the top cell and at the top cell / interconnect layer interface, but also promotes efficient carrier recombination at the interconnect layer by improving the surface potential distribution of the top cell, thus reducing the series resistance of the tandem device. Finally, the reduction in defect state density decreases non-radiative recombination losses in the top cell, allowing more photogenerated carriers to be successfully injected into the bottom cell through the interconnect layer, thereby simultaneously improving the open-circuit voltage, short-circuit current density, and fill factor of the tandem device. The synergistic effect of these multiple effects enables the photoelectric conversion efficiency of the all-perovskite tandem device to exceed 30%, demonstrating the enormous application potential of this additive strategy in the field of high-efficiency tandem photovoltaics.
[0076] Example 3: Fabrication of a single-junction 1.68 eV bandgap perovskite solar cell
[0077] The difference between Example 3 and Example 1 is that step S2 in Example 3 is as follows: S2: Deposition of wide-bandgap perovskite films using a two-step spin-coating process: A perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide was spin-coated at 500 rpm for 2 s, followed by spin-coating at 4000 rpm for 60 s. In the second spin-coating step, 150 μL of ethyl acetate as an antisolvent was added dropwise at the 25th second. The film was then thermally annealed at 120 °C for 20 min under a N2 atmosphere to form a perovskite film containing benzothiadiazole-4,7-dicarboxyhydrazide with the molecular formula FA. 0.8 Cs 0.2 PbI 2.4 Br 0.6 The perovskite layer. The perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide was prepared as follows: N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) were mixed in a volume ratio of 3:1 to prepare a mixed solvent. Then, FAI (178.88 mg), PbBr2 (143.13 mg), PbI2 (419.51 mg), and CsI (67.6 mg) were dissolved in 1 mL of the mixed solvent to form a perovskite precursor solution with a concentration of 1.3 mol / L. Then, benzothiadiazole-4,7-dicarboxyhydrazide was dissolved in the prepared perovskite precursor solution at a concentration of 0.8 mg / mL.
[0078] Steps S1 and S3 are the same as in Example 1. A single-junction perovskite solar cell with a bandgap of 1.68 eV is prepared.
[0079] Comparative Example 3 The fabrication of the single-junction 1.68 eV bandgap perovskite solar cell in Comparative Example 3 differs from that in Example 3 in that, in step S2 of Comparative Example 3, the perovskite precursor solution used did not contain benzothiadiazole-4,7-dicarboxyhydrazide, and a wide bandgap perovskite film was deposited directly using a two-step spin-coating process with a 1.3 mol / L perovskite precursor solution. All other steps were the same as in Example 3.
[0080] Example 4: Fabrication of a single-junction 1.85 eV bandgap perovskite solar cell
[0081] The difference between Example 4 and Example 1 is that step S2 in Example 4 is as follows: S2: Deposition of wide-bandgap perovskite films using a two-step spin-coating process: A perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide was spin-coated at 500 rpm for 2 s, followed by spin-coating at 4000 rpm for 60 s. In the second spin-coating step, 150 μL of ethyl acetate as an antisolvent was added dropwise at the 25th second. The film was then thermally annealed at 120 °C for 20 min under a N2 atmosphere to form a perovskite film containing benzothiadiazole-4,7-dicarboxyhydrazide with the molecular formula FA. 0.66 Cs0.06 MA 0.28 PbI 1.5 Br 1.5 The perovskite layer. The perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide was prepared as follows: N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) were mixed in a volume ratio of 4:1 to prepare a mixed solvent. Then, FAI (113.5 mg), MABr (31.35 mg), PbBr2 (223.88 mg), PbI2 (179.79 mg), and CsI (15.59 mg) were dissolved in 1 mL of the mixed solvent to form a perovskite precursor solution with a concentration of 1.0 mol / L. Then, benzothiadiazole-4,7-dicarboxyhydrazide was dissolved in the prepared perovskite precursor solution at a concentration of 1.5 mg / mL.
[0082] Steps S1 and S3 are the same as in Example 1. A single-junction perovskite solar cell with a bandgap of 1.85 eV is prepared.
[0083] Comparative Example 4 The fabrication of the single-junction 1.85 eV bandgap perovskite solar cell in Comparative Example 4 differs from that in Example 4 in that, in step S2 of Comparative Example 4, the perovskite precursor solution used did not contain benzothiadiazole-4,7-dicarboxyhydrazide, and a wide bandgap perovskite film was deposited directly using a two-step spin-coating process with a 1.2 mol / L perovskite precursor solution. All other steps were the same as in Example 4.
[0084] To verify the universality of benzothiadiazole-4,7-dicarboxyhydrazide as a wide-bandgap perovskite additive, Examples 3 and 4 introduced this additive into two wide-bandgap perovskite systems with different bandgaps of 1.68 eV and 1.85 eV, respectively, with a control group not incorporating benzothiadiazole-4,7-dicarboxyhydrazide. JV performance tests (0 V–1.4 V forward and reverse scans) were performed on the above devices, and the results are attached. Figure 6 , 7 As shown in Table 3, for the 1.68 eV bandgap system, after modification with benzothiadiazole-4,7-dicarboxyhydrazide, the device efficiency increased from 16.9068% in the control group to 19.7157%, and the open-circuit voltage increased from 1.2152 V to 1.2822 V; for the 1.85 eV bandgap system, the device efficiency increased from 16.3632% in the control group to 18.5693%, and the open-circuit voltage increased from 1.2682 V to 1.3252 V. Both bandgap systems showed significant improvements in device efficiency and open-circuit voltage, and the hysteresis effect was significantly reduced.
[0085] Table 3 Performance data of solar cells prepared in Examples 3-4 and Comparative Examples 3-4
[0086] The above results demonstrate that benzothiadiazole-4,7-dicarboxyhydrazide, as an additive for modifying wide-bandgap perovskites, has good versatility and can be widely applied in wide-bandgap perovskite photovoltaic devices with different band gaps (1.65–1.85 eV range) and different composition systems, providing a general strategy for performance optimization of various wide-bandgap perovskite optoelectronic devices.
[0087] All aspects, embodiments, and features of this invention should be considered illustrative in all respects and not limiting of the invention; the scope of the invention is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.
[0088] In the preparation method of this invention, the order of the steps is not limited to the listed order. For those skilled in the art, variations in the order of the steps without creative effort are also within the scope of protection of this invention. Furthermore, two or more steps or actions can be performed simultaneously.
[0089] Finally, it should be noted that the specific embodiments described herein are merely illustrative examples of the invention and are not intended to limit the implementation of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them; it is neither necessary nor possible to exemplify all embodiments here. However, these obvious variations or modifications derived from the essential spirit of the invention still fall within the scope of protection of the invention, and interpreting them as any additional limitation would contradict the spirit of the invention.
Claims
1. A perovskite solar cell modified with benzothiadiazole-4,7-dicarboxyhydrazide, characterized in that, The system comprises a substrate, a first hole transport layer, a first perovskite active layer, a first electron transport layer, a first electron modification layer, and a first electrode, which are sequentially stacked. The first perovskite active layer contains benzothiadiazole-4,7-dicarboxyhydrazide, the molecular structure of which is: ; The perovskite solar cell is a wide-bandgap perovskite solar cell, and the optical bandgap of its first perovskite active layer is 1.65~1.85 eV.
2. The perovskite solar cell modified with benzothiadiazole-4,7-dicarboxyhydrazide according to claim 1, characterized in that, The materials of the first perovskite active layer include benzothiadiazole-4,7-dicarboxyhydrazide and materials with the general formula FA. 1-x- y Cs x MA y PbI 3-z-a Br z Cl a The perovskite material, wherein 0≤x≤0.4, 0≤y≤0.4, 0.2≤z≤1.5, and 0≤a≤1.
5.
3. The perovskite solar cell modified with benzothiadiazole-4,7-dicarboxyhydrazide according to claim 1, characterized in that, The first perovskite active layer is formed by coating a first perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide, wherein the concentration of benzothiadiazole-4,7-dicarboxyhydrazide in the first perovskite precursor solution is 0.1~5.0 mg / mL.
4. The perovskite solar cell modified with benzothiadiazole-4,7-dicarboxyhydrazide according to claim 1, characterized in that, The preparation method of the benzothiadiazole-4,7-dicarboxyhydrazide includes the following steps: (1) Benzothiadiazole-4,7-dicarboxylic acid reacts with an alcohol solvent under the catalysis of an acid catalyst to give an intermediate product; (2) Dissolve the intermediate product obtained in step (1) in an organic solvent, add hydrazine hydrate, and carry out hydrazinolysis to obtain benzothiadiazole-4,7-dicarboxyhydrazide.
5. The perovskite solar cell modified with benzothiadiazole-4,7-dicarboxyhydrazide according to claim 4, characterized in that, The alcohol solvent in step (1) is a C1-C4 aliphatic monohydric alcohol, including one or more of methanol, ethanol, n-propanol, isopropanol, and n-butanol; the acid catalyst includes concentrated sulfuric acid with a mass fraction of 95-98 wt% and / or concentrated hydrochloric acid with a mass fraction of 35-38 wt%; the molar ratio of benzothiadiazole-4,7-dicarboxylic acid to the acid catalyst is 1:(1-3); the esterification reaction temperature is 50-80℃, and the reaction time is 8-16 h; In step (2), the organic solvent is one or more of methanol, ethanol, n-propanol, isopropanol, and n-butanol; the hydrazine hydrate is an aqueous solution of hydrazine hydrate with a mass fraction of 50-85 wt%; the molar ratio of the intermediate product to hydrazine hydrate is 1:(5-10); the reaction temperature of the hydrazine hydrolysis reaction is 60-80℃, and the reaction time is 6-12h.
6. The method for preparing a perovskite solar cell modified with benzothiadiazole-4,7-dicarboxyhydrazide as described in any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Prepare the first hole transport layer on the substrate; S2. Prepare a first perovskite precursor solution by adding benzothiadiazole-4,7-dicarboxyhydrazide to the first perovskite precursor solution and mixing it evenly to obtain a first perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide. S3. Spin-coat the first perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide onto the surface of the first hole transport layer, and anneal the solution to form the first perovskite active layer. S4. A first electron transport layer, a first electron modification layer and a first electrode are sequentially prepared on the first perovskite active layer to obtain the perovskite solar cell.
7. The preparation method according to claim 6, characterized in that, The solvent for the first perovskite precursor solution is a polar aprotic organic solvent selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone. And / or, in the first perovskite precursor solution, Pb 2+ The concentration is 0.5~2.0 mol / L; And / or, in the first perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide, the concentration of benzothiadiazole-4,7-dicarboxyhydrazide is 0.1~5.0 mg / mL; And / or, in step S3, the spin coating adopts a two-step spin coating process: the first step is spin coating at 400~1000 rpm for 1~10 s, and the second step is spin coating at 3000~5000 rpm for 40~70 s, and the anti-solvent is added dropwise at the 20~30 s of the second spin coating; the anti-solvent is selected from one or more of ethyl acetate, chlorobenzene, toluene, and anhydrous diethyl ether; And / or, the annealing treatment is performed at a temperature of 100~140℃ for a time of 10~30 min.
8. A fully perovskite tandem solar cell, characterized in that, It includes a top battery sub-unit, an intermediate interconnect layer, and a bottom battery arranged in sequence; The top-mounted battery sub-unit includes a substrate, a first hole transport layer, a first perovskite active layer, and a first electron transport layer stacked sequentially. The first perovskite active layer contains benzothiadiazole-4,7-dicarboxyhydrazide, and the optical band gap of the first perovskite active layer is 1.65~1.85 eV. The bottom cell includes a second hole transport layer, a second perovskite active layer, a second electron transport layer, a second electron modification layer, and a second electrode, which are stacked sequentially; the optical band gap of the second perovskite active layer is 1.2~1.4 eV; The intermediate interconnect layer is stacked on the surface of the first electron transport layer of the top battery sub-cell.
9. The all-perovskite tandem solar cell according to claim 8, characterized in that, The material of the second perovskite active layer includes materials with the general formula FA. 1-x-y Cs x MA y Pb 1-b Sn b I 3-z-a Br z Cl a The perovskite material, wherein 0≤x≤0.4, 0≤y≤0.4, 0<b≤0.6, 0≤z≤1.5, 0≤a≤1.5; And / or, the bottom cell further includes a perovskite modification layer located between the second perovskite active layer and the second electron transport layer, wherein the perovskite modification layer is made of ethylenediamine dihydroiodide and 1,4-butanediamine hydroiodate.
10. A method for preparing an all-perovskite tandem solar cell as described in claim 8, characterized in that, Includes the following steps: S1. Prepare the first hole transport layer on the substrate; S2. Prepare a first perovskite precursor solution by adding benzothiadiazole-4,7-dicarboxyhydrazide to the first perovskite precursor solution and mixing it evenly to obtain a first perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide. S3. Spin-coat the first perovskite precursor solution containing benzothiadiazole-4,7-dicarboxyhydrazide onto the surface of the first hole transport layer, and anneal the solution to form the first perovskite active layer. S4. Prepare the first electron transport layer on the first perovskite active layer to obtain the top cell sub-unit; S5. An intermediate interconnect layer is fabricated on the surface of the first electron transport layer of the top battery sub-cell; S6. Prepare a second hole transport layer on the surface of the intermediate interconnect layer, and then deposit a second perovskite active layer. S7. A second electron transport layer, a second electron modification layer and a second electrode are sequentially prepared on the surface of the second perovskite active layer to obtain a fully perovskite tandem solar cell.